Chitosan and deoxy-starch as polymeric matrixes for immobilization of bioactive components - V. A. Kuznetsov; A. I. Slivkin; V. L. Lapenko; A. A. Bolgov (Тонкие химические технологии, 2009)
Introduction in structure of drugs carbohydrate components lead to increasing solubility in water, detoxication and prolongation of biological action in organism. Method of synthesis polymeric forms of isoniazid include reaction oligochitosan, N-hydroxymethylchitosan and N-chloro-2- hydroxypropylchitozan with antiphthisic substance. Hydrophilic polymeric base of streptomycin sulfate was prepared by reactions chitosan with antibiotics sulfate. Synthesized water-soluble analogues of 1,4-β-2-amino-2-desoxy-D-glucan with side chains containing amino acids with the formation of covalent linkage through methylene or hydroxypropylene spacer. As a polymer matrix for the immobilization of glycine, L-lysine and its hydrochloride, L-glutamic acid used chitosan, Nhydroxymethylchitosan, N-chloro-2-hydroxypropylchitosan and 3-hydroxymethyl-3-deoxy-starch.